Bridging the digital learning resources gap through multimedia utilization using ict principles in instruction - Soepriyanto, Yerry; Praherdhiono, Henry (2015)
The most crucial gap is the technology gap. The gap is a picture of the condition between presence and absence 1) Internet access, 2) telephone network.The concept of ICT in learning does not require digital learning resources available online. The principle of the development of instructional mediarealize the digital learning resources in a multimedia format. Results of the development of digital learning resources in a multimedia format involving the simultaneous use by multiple media formats. Multimedia does not make the narrow paradigm behwa digital learning resources more effectively be achieved through presentations that are informative. The main focus of the multimedia design using the concept of plural media, so that the information presented in various formats both characterized on-line and off-line. Keywords: Inequality, ICT, Multimedia